1936
DOI: 10.1111/j.1365-2621.1936.tb17765.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C Content of Vegetables. I. Spinach*

Abstract: Fresh spinach has long been known t o contain relatively large amounts of vitamin C ; however, the amounts reported by the several workers differ greatIy. One difficulty in comparing the published results lies jn the fact that there is littIe uniformity in the mode of reporting the data obtained. Most analyses reported recently have indicated the amounts of ascorbic acid in milligrams per gram of spinach. If one assumes, as suggested by Bessey and King (1933), that 0.5 mg. of a.scorbic acid per day is required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1936
1936
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…While i t is probable that variations in technique may account for some of the differences in the results obtained, yet it is also probable that cabbage does vary widely in its ascorbic-acid content. In the case of spinach and peas it has been found that variety and freshness are important factors controlling the vitamin-C: content of these vegetables, as reported by Tressler, Mack, and King (1936) and Mack, Tressler, and Eing (1936).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…While i t is probable that variations in technique may account for some of the differences in the results obtained, yet it is also probable that cabbage does vary widely in its ascorbic-acid content. In the case of spinach and peas it has been found that variety and freshness are important factors controlling the vitamin-C: content of these vegetables, as reported by Tressler, Mack, and King (1936) and Mack, Tressler, and Eing (1936).…”
Section: Introductionmentioning
confidence: 86%
“…In the case of spinach and peas it has been found that variety and freshness are important factors controlling the vitamin-C: content of these vegetables, as reported by Tressler, Mack, and King (1936) and Mack, Tressler, and Eing (1936).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The curative method described previously by Tressler, Mack, and King (1936) was used with the exception that the curative feeding period was extended to 21 days.…”
Section: Fentopi' Tressler C a X P A N D Kingmentioning
confidence: 99%
“…Spinach is a highly perishable product with multiple nutrients such as minerals (Bhattacharjee et al, ), vitamins (Bunea et al, ; Tang, Qin, Dolnikowski, Russell, & Grusak, ; Tressler, Mack, & King, ), carotenes (Bunea et al, ; Lim, ), and antioxidant phenolic compounds (Pandjaitan, Howard, Morelock, & Gil, ). Spinach is widely consumed and forms a major part of human diet due to its nutritional properties.…”
Section: Introductionmentioning
confidence: 99%